2020
DOI: 10.1007/s11695-020-04892-8
|View full text |Cite
|
Sign up to set email alerts
|

Internal Herniation Incidence After RYGB and the Predictive Ability of a CT Scan as a Diagnostic Tool

Abstract: Purpose The clinical diagnosis of an internal herniation (IH) after a Roux-en-Y Gastric Bypass (RYGB) remains difficult; therefore, performing a CT scan is usually part of the diagnostic process. The goal of this study was to assess the incidence of IH in patients with open and closed MD (mesenteric defect) and to study if the ability to diagnose an IH with a CT scan is different between these groups. Materials and Methods IH was defined as a visible intestine through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 30 publications
(39 reference statements)
0
13
1
Order By: Relevance
“…The number of radiologists analyzing CT scans variated from 1 to 3 radiologists. Exploratory surgery combined with a negative clinical follow-up following the CT scan was used as a reference standard in 5 studies, 10,22,33,36,40 whereas the remaining studies used exploratory surgery only 8,12,13,15,16,19,32,34,35,38,39,41–43 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of radiologists analyzing CT scans variated from 1 to 3 radiologists. Exploratory surgery combined with a negative clinical follow-up following the CT scan was used as a reference standard in 5 studies, 10,22,33,36,40 whereas the remaining studies used exploratory surgery only 8,12,13,15,16,19,32,34,35,38,39,41–43 …”
Section: Resultsmentioning
confidence: 99%
“…Six of the included studies specifically reported on patients who presented with acute symptoms, 8,15,32,33,35,36 7 studies on patients with both acute and intermittent symptoms, 10,12,13,19,34,37,38,42 1 study specifically focused on patients with intermittent complaints suggestive of IH, 39 and 5 studies did not specify the duration or type of onset of symptoms 16,22,40,41,43 . A CT of the abdomen was performed in all patients with symptoms of IH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations